Morphological Study For Specie Of Genus Adiantum L. Pteridaceae Growing In Some Areas In Lattakia – Syria (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2020)
At this study, one specie of genus Adiantum L. have been recorded, that it was: Adiantum capillus- veneris L. This  specie was recorded for the first time in different areas in Lattakia. And this specie was not recorded by moutterde in this places. The morphological features were used to separate the specie (the sporophyte and gametophyte, measurement the leaves and shapes, number of the pinnules and measurements, the petiole of leave, the sori and sporangium, shapes of the spores and measurements, antheridia and archegonia). This study showed that: the life cycle need of 100 days for growing, and the humidity was very important for growing and increase this plant and spread it, also it prefers the limy rocks . تمّ جمع نوع واحد من جنس كزبرة البئر في هذه الدراسة وهو: النوع كزبرة البئر الجنوبي أو شعر البنات A.capillus- veneris L.  من مناطق مختلفة في الساحل السوري وتم تسجيل وجوده لأول مرة في هذه المناطق. مع العلم أن العالم موتيرد لم يحدد انتشاره في أي منطقة من مناطق الساحل السوري عند دراسته للفلورا اللبنانية السورية. تمّ تحديد النوع بالاعتماد على الصفات المورفولوجية ( الشكل الحياتي، بنية النبات البوغي والعروسي، أبعاد الأوراق وأشكالها، عدد الوريقات وأبعادها، معلاق الورقة، البقع والأكياس البوغية، الأبواغ وأبعادها وأشكالها، المناطف والأرحام). أوضحت الدراسة أن دورة حياة هذا النوع تستغرق 100 يوم ، كما لوحظ أن عامل الرطوبة مهم بشكل كبير لنمو وتكاثر هذا النوع وانتشاره بالإضافة أنه يفضل التربة الكلسية.